2019
DOI: 10.1021/acscatal.9b02863
|View full text |Cite
|
Sign up to set email alerts
|

Flavin Bioorthogonal Photocatalysis Toward Platinum Substrates

Abstract: Catalytic reactions that use metal complexes as substrates, rather than catalysts, are nearly unknown. We recently demonstrated that certain flavins (FLs) are potent redox photocatalysts capable of converting Pt IV anticancer prodrug complexes into Pt II drugs in the biological environment. Herein, we investigate the mechanism of these artificial photocatalytic reactions employing four different free flavins, namely riboflavin (Rf), flavin mononucleotide (FMN), tetra-O-acetyl riboflavin (TARF) and lumiflavin (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
65
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 43 publications
(69 citation statements)
references
References 45 publications
1
65
0
Order By: Relevance
“…51 We discuss these recent developments including detailed mechanisms of action, along with recent work on in-cell photo-catalytic reduction of metal complexes by flavines. 20,[52][53][54][55] Coenzymes NAD + /NADH play important roles in maintaining the intracellular redox balance and mitochondrial electron transport chain, and such in-cell transfer hydrogenation catalysts might find application in biotechnology and therapy, for example as catalytic anticancer drugs.…”
Section: Introductionmentioning
confidence: 99%
“…51 We discuss these recent developments including detailed mechanisms of action, along with recent work on in-cell photo-catalytic reduction of metal complexes by flavines. 20,[52][53][54][55] Coenzymes NAD + /NADH play important roles in maintaining the intracellular redox balance and mitochondrial electron transport chain, and such in-cell transfer hydrogenation catalysts might find application in biotechnology and therapy, for example as catalytic anticancer drugs.…”
Section: Introductionmentioning
confidence: 99%
“…1A) which is the active catalyst prompting the bioorthogonal substrate conversion. 11,13 In vitro experiments also demonstrated that this activation strategy hold promise for its capacity to deliver lethal concentrations of Pt drugs with minimal light doses. 11,16 The relevance of Pt(IV) complexes in photochemotherapy research is proved by the numerous photoactivatable prodrugs and activation approaches developed in recent years.…”
mentioning
confidence: 97%
“…As previously reported, FMN alone cannot catalytically reduce 1 in the absence of light, nor under light irradiation without electron donor. 13 Controls showed that TACN AuNPs only prompted a 15% substrate conversion in the dark, both with and without FMN loaded ( Fig. S7 and S8, ESI †).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…(a) General photocatalytic mechanism for the Pt(IV) prodrug activation by flavins; R1 = e.g. ribityl, ribityl phosphate, R2 = adenosine diphosphate ribose and R3 = CH2CH2COOH (1) or CH3 (2). (b) mSOG's molecular model based on the structure of iLOV protein (PBD ID: 6GPU).…”
mentioning
confidence: 99%